Rehabilitation of Dysphagia Following Head and Neck Cancer - Pauloski, Barbara R. (2008)
Patients with cancers of the oral cavity, pharynx or larynx may be treated with surgery, radiotherapy, chemotherapy, or a combination of these modalities. Each treatment type may have a negative impact on posttreatment swallowing function; these effects are presented in this chapter. The clinician has a number of rehabilitative procedures available to reduce or eliminate swallowing disorders in patients treated for cancer of the head and neck. The various procedures--including postures, maneuvers, modifications to bolus volume and viscosity, range of motion exercises, and strengthening exercises--and their efficacy in treated head and neck cancer patients are discussed.